2020
DOI: 10.2139/ssrn.3565521
|View full text |Cite
|
Sign up to set email alerts
|

How Does Household Spending Respond to an Epidemic? Consumption During the 2020 COVID-19 Pandemic

Abstract: excellent research assistance. This draft is preliminary and comments are welcome. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 5 publications
1
31
0
2
Order By: Relevance
“…This result is line with earlier studies such as not only by Austrian et al (2020) who have shown that lower-income people have experienced less social distancing due to fear of losing income during COVID-19 but also by Borjas (2020) who has shown that the likelihood that a test was positive was larger in predominantly black neighbourhoods in New York City. The results are also supported by other studies such as by Baker et al (2020) who have shown that higher-income people move less and thus spend less in restaurants, groceries or retailers during COVID-19 or by Bonaccorsi et al (2020) who have shown that mobility contraction is stronger in municipalities, where inequality is higher and income per capita is lower, or by Srichan et al (2020) who have shown that the level of education, occupation or income is associated with how people experience social distancing during COVID-19. Important policy implications follow, especially when it is considered that higher-educated, higher-income or Asian people were able to work at home and maintain employment during COVID-19 due to their occupations as suggested in studies such as by Bick, Blandin, and Mertens (2020) or Dingel and Neiman (2020), whereas lower-educated workers, Blacks or Hispanics were not able to work at home due to their occupations and thus became unemployed as suggested in studies such as by Gupta et al (2020) or Yasenov (2020).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…This result is line with earlier studies such as not only by Austrian et al (2020) who have shown that lower-income people have experienced less social distancing due to fear of losing income during COVID-19 but also by Borjas (2020) who has shown that the likelihood that a test was positive was larger in predominantly black neighbourhoods in New York City. The results are also supported by other studies such as by Baker et al (2020) who have shown that higher-income people move less and thus spend less in restaurants, groceries or retailers during COVID-19 or by Bonaccorsi et al (2020) who have shown that mobility contraction is stronger in municipalities, where inequality is higher and income per capita is lower, or by Srichan et al (2020) who have shown that the level of education, occupation or income is associated with how people experience social distancing during COVID-19. Important policy implications follow, especially when it is considered that higher-educated, higher-income or Asian people were able to work at home and maintain employment during COVID-19 due to their occupations as suggested in studies such as by Bick, Blandin, and Mertens (2020) or Dingel and Neiman (2020), whereas lower-educated workers, Blacks or Hispanics were not able to work at home due to their occupations and thus became unemployed as suggested in studies such as by Gupta et al (2020) or Yasenov (2020).…”
supporting
confidence: 83%
“…characteristics such as age groups due to the way that COVID-19 affects people of alternative ages (e.g., see Dowd et al, 2020), in practice, knowledge and attitudes have been different across other demographic characteristics such as income, education, race, ethnicity, gender, occupation, population, and place of current residence. 1 Since economic activity is highly related to mobility as indicated by studies such as by Baker, Farrokhnia, Meyer, Pagel, and Yannelis (2020), these developments imply potential redistributive effects of COVID-19 across demographic groups that require the attention of policy-makers.…”
mentioning
confidence: 99%
“…According to the most recent sociological literature on the pandemic's effects (see, among others, [6,9,10]), due to lifestyle changes and restrictions imposed by the authorities, consumers have partially changed their consumption habits, moving towards specific products/services or reducing the frequency of purchase of certain goods. As Boons et al [11] (p. 3) also point out: "the Covid-19 crisis and the response of 'lockdown' has globally disrupted the normality of everyday lives, resulting in people abstaining from previous practices, or altering and substituting them; they also learn and adapt to new practices and ways to coordinate and organize everyday lives within the home".…”
Section: Methodsmentioning
confidence: 99%
“…Consumer discretionary spending is in free fall as non-essential businesses are closed and individuals are saving more. Analyzing data from a personal finance website, (Baker et al 2020) found that consumer spending in the United States is highly dependent on the severity of the disease's outbreak in the state and the strength of the local government's response.…”
Section: Introductionmentioning
confidence: 99%